2013
DOI: 10.1155/2013/683174
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Frequency Azimuthally Stable Cartography of Biological Polycrystalline Networks

Abstract: A new azimuthally stable polarimetric technique processing microscopic images of optically anisotropic structures of biological tissues histological sections is proposed. It has been used as a generalized model of phase anisotropy definition of biological tissues by using superposition of Mueller matrices of linear birefringence and optical activity. The matrix elementM44has been chosen as the main information parameter, whose value is independent of the rotation angle of both sample and probing beam polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 14 publications
0
31
0
3
Order By: Relevance
“…Based on the synthesis of theoretical 30,31 and experimental [23][24][25][26][27][28][29]38,39 results, we obtained algorithms for complex Jones-matrix reconstruction of the distributions of both phase (LB 0;90 ; LB 45;135 ; CB ;È ) and amplitude (LD 0;90 ; LD 45;135 ; CD ;È ) anisotropy of polycrystalline¯lms of biological°u ids…”
Section: Methods and Materials 21 Basic Equations And Theoretical Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the synthesis of theoretical 30,31 and experimental [23][24][25][26][27][28][29]38,39 results, we obtained algorithms for complex Jones-matrix reconstruction of the distributions of both phase (LB 0;90 ; LB 45;135 ; CB ;È ) and amplitude (LD 0;90 ; LD 45;135 ; CD ;È ) anisotropy of polycrystalline¯lms of biological°u ids…”
Section: Methods and Materials 21 Basic Equations And Theoretical Rmentioning
confidence: 99%
“…Previously, we found that method of direct polarization mapping of microscopic images of biological°uid¯lms (blood plasma, synovial°uid, liquor) is sensitive to pathological changes in human organs. [23][24][25][26][27][28] Further development of these studies allowed the Jones-matrix reconstruction of the distributions of linear and circular birefringence of polycrystalline bile¯lms. 29 Thus, this method can be used for diagnostics of Type II diabetes with excellent accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…HE optically-based polarimetry is popular experimental approach widely used for non-invasive diagnosis of various turbid tissue-like scattering media [1][2][3][4][5][6], including those containing optically anisotropic layers [7][8][9] and fluids [10][11][12]. With the recent instrumentation developments in the field, a high sensitivity of laser polarimetry in screening of turbid cancerous biological tissues has been achieved [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the frame of these studies, a development of algorithms for reconstructing the distributions of phase and amplitude anisotropy parameters of the protein polycrystalline networks of sampling layers have been performed. Later, the potential of this diagnostic approach has been demonstrated [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%